Recent results of beam loss mitigation and extremely low beam loss operation of J-PARC RCS. Issue 1 (1st January 2023) - Saha, P K; Okabe, K; Nakanoya, T; Shobuda, Y; Harada, H; Tamura, F; Okita, H; Yoshimoto, M; Hotchi, H
Abstract: In the 3-GeV RCS (Rapid Cycling Synchrotron) at J-PARC (Japan Proton Accelerator Research Complex), multi-turn H − charge-exchange injection is performed by using a thin stripped foil. The residual radiation at the injection area caused by the uncontrolled beam loss occurred by foil scattering of the circulating beam is a serious issue for regular maintenance works. In addition, the beam loss at the collimator section and its downstream caused for a large emittance beam also should be reduced, especially at high intensity operation. For that purpose we have minimized injection beam size and implemented a smaller size stripper foil. The circulating beam hitting rate is reduced by using a smaller foil, while an optimized vertical angle of the smaller injection beam for vertical transverse painting also gave a reduction of the circulating beam emittances and resulted a further significant beam loss mitigation at the collimator section and its downstream. As a result, the residual radiation after user operation at 700 kW beam power was also measured to be significantly reduced.